BLENDED LEARNING SEBAGAI ALTERNATIF PEMBELAJARAN DI ERA DIGITAL - I Ketut Widiara (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Blended learning is a learning strategy that aims to achieve goals by combining classroombasedlearning / face to face with technology-based learning and information that is done online.So far, the popular learning strategy in Indonesia is traditional class based learning (classical)by using lecture method. The addition of the right learning innovation will result in the selfrelianceand self-confidence of students who have tried to explore and explore not only the teachers.This assumption is what leads blended learning to be an option without learning not enough justby face to face.Keywords: Blended Learning, Learning, Learning Strategy